2013
DOI: 10.1016/j.exger.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the activin A–myostatin–follistatin system on aging bone and muscle progenitor cells

Abstract: The activin A-myostatin-follistatin system is thought to play an important role in the regulation of muscle and bone mass throughout growth, development, and aging; however, the effects of these ligands on progenitor cell proliferation and differentiation in muscle and bone are not well understood. In addition, age-associated changes in the relative expression of these factors in musculoskeletal tissues have not been described. We therefore examined changes in protein levels of activin A, follistatin, and myos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 36 publications
2
54
0
Order By: Relevance
“…A recent in vitro study has pointed out the close interaction between skeletal muscle myokines and bone marrow-derived cell function (44). Maintenance of skeletal muscle health status has been shown to have an influence on systemic age-related disorders (45).…”
Section: Myokines As Therapeutic and Pharmacologic Targetsmentioning
confidence: 99%
“…A recent in vitro study has pointed out the close interaction between skeletal muscle myokines and bone marrow-derived cell function (44). Maintenance of skeletal muscle health status has been shown to have an influence on systemic age-related disorders (45).…”
Section: Myokines As Therapeutic and Pharmacologic Targetsmentioning
confidence: 99%
“…Both myostatin and activin A share follistatin as their antagonist (Vamvini et al, 2011). As activin A, myostatin and follistatin are sensitive to age-and disease-associated muscle changes, they might play an important role in the development of sarcopenia (Bowser et al, 2013). Recently, another member of the TGF-β superfamily, the growth and differentiation factor-15 (GDF-15), has been described as a potential novel mediator of muscle wasting (Tsai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in our lab showed that myostatin can inhibit the proliferation of aged bone marrow stromal cells (Bowser et al, 2013), that bone marrow stromal cells from mice lacking myostatin show increased proliferation , and that myostatin can inhibit chondrogenesis in vivo and in vitro (Elksrawy et al, 2012). These data may at least in part explain the increased fracture callus size following osteotomy in mice lacking myostatin , and increased fracture callus bone volume in mice treated with myostatin propeptide following osteotomy .…”
Section: Discussionmentioning
confidence: 99%